Analysis of Service Quality on the Satisfaction of the Health Social Security Administration’s Inpatients - Harefa, Fredy Elvan Adi Putra; Utami, Tri Niswati; Moriza, Tengku (Journal La Medihealtico, 2023)
The problem that is often faced by hospitals as a place for health services is that they have not been able to provide something that is really expected by service users. So that complaints of dissatisfaction or patient complaints are often found in the process of providing health services. The purpose of this study was to analyze the quality of service on the satisfaction of BPJS inpatients at Bethesda General Hospital Gunungsitoli Nias. This research uses quantitative research with cross sectional design. The study population was BPJS inpatients at Bethesda Gunungsitoli Hospital, the sample using the Accidental Sampling technique was n = 165 people. This study used a questionnaire. The analysis of this study used univariate, bivariate and multivariate. The statistical test used was the chi square test and logistic regression. The results of the chi-square test were obtained on the variables of tangiable health service quality (p=0.000), reliability (p=0.000), responsiveness (p=0.000), assurance (p=0.000), attention (p=0.000) indicating a quality relationship service on satisfaction of BPJS inpatients at Bethesda Gunungsitoli General Hospital. The most influential variable with satisfaction is reliability p = 0.031 Exp (B 6.623) with an OR value of 25.234 (10.213-62.314). Based on these results, it was concluded that there was a relationship between service quality and satisfaction of BPJS inpatients at Bethesda Gunungsitoli General Hospital.